Особливості розвитку інноваційної інфраструктури України - Степанюк, Н. А. (Видавництво Львівської політехніки, 2015)
Виділено основні завдання інноваційної інфраструктури, що мають виконуватися в Україні. Досліджено сучасний регіональний підхід до формування інноваційної структури в Україні. Проаналізовано іноземний досвід створення і розвитку інноваційної інфраструктури. Запропоновано створення національної інноваційної системи, яка забезпечить сприятливий інноваційний клімат для розвитку інноваційної інфраструктури. The article distinguish the main tasks of innovation infrastructure that must be carry out in Ukraine. The modern regional approach to the forming of innovation structure in Ukraine is researched. There is analyzed international experience of creation and development of innovation infrastructure in it. In the artile it is offered an establishment of a national innovation system that it will provide a favorable innovation climate for development of innovation infrastructure. Ukraine stands in the way of innovation development of economy and choice in this country. Significant natural resources in Ukraine, the use of which would give the opportunity to build on this basis its development there. It is necessary to realize their intellectual potential, which is the basis of innovation economy and increase its competitiveness. The innovation process in developed countries – is that combining science, technology, economics, business, management, covering the full range of relations of production, exchange, consumption. Behind all this is a series of interconnected organizations small and large companies, universities, laboratories, technology parks and incubators, engaged in the production and conversion of scientific knowledge and technology on a commercial basis. The main source of innovations is the scientific and technical activities, to bridge the implementation of technology in the real economy – technology transfer, and the main player in innovation – research institutions, universities that turn new knowledge into value added tax and wealth.
Features of developing innovative infrastructure in Ukraine
Keywords: інновації; інноваційна інфраструктура; технопарки; інфраструктура; науковий центр; innovations; innovation infrastructure; industrial parks; infrastructure; research center